Meeting report of the International Policy Dialogue on HIV/AIDS and Disability - Peake, Sharon (The International AIDS Society, 2009)
As part of a partnership arrangement with the Joint United Nations Programme on HIV/AIDS and the Public Health Agency of Canada, Health Canada hosted an International Policy Dialogue on HIV/AIDS and Disability from 11 to 13 March 2009 in Ottawa, Canada. The dialogue provided a forum for stakeholders from governments, academia, and non-governmental and multilateral organizations to explore the issues and evidence related to HIV/AIDS and disability, and to chart a way forward in terms of policy and programme development. This meeting report outlines the participants, objectives and high-level outcomes.